Le voyage à travers l’histoire dans l’oeuvre romanesque de Françoise Lalande - Zbierska-Mościcka, Judyta (Studia Romanica Posnaniensia, 2012)
From "Daniel ou Israël" (1987) through "Noir" (2000) and "Une Belge méchante" (2007) and as far as to "La séduction des hommes tristes" (2010) Françoise Lalande’s narratives aspire to give account of the history of human kind, not limited by any specific time or space. In her works, Europe’s history is mixed with history of the world, social with political history, the ancient one describing fate of the Jews with present times, giving account of the events happening before our eyes. The author, convinced of writer’s necessary involvement, reacts to all signs of injustice and brutality so characteristic for the 20th century’s history. Lalande tells us how to live the history playing, according to the author, a key role in creation of our identity. Something that she, as a Jew herself and citizen of the world, is fully aware of.